ANALISIS HUKUM PENGEMBANGAN POTENSI WISATA PANTAI JAYANTI CIANJUR TERHADAP KEWENANGAN PEMERINTAH KABUPATEN CIANJUR - Asep Hasanudin (Jurnal Hukum Mimbar Justitia, 2019)
This study aims to describe the form of policies, problems encountered, and efforts that must be developed by the Regional Government of Cianjur Regency in the Development of Jayanti Tourism Potential as a tourism asset. The method of approach used in this research is Normative Jurisprudence, namely by studying and reviewing the principles of law, especially positive legal principles derived from existing literature from legislation and provisions, especially relating to tourism. Tourism is a temporary and  short-term  transformation  of  people  towards  destinations  outside  the  place where they live and work. With the Law of the Republic of Indonesia Number 10 of 2009 Concerning Tourism and bearing in mind that Tourism is an inseparable part of national development, the tourism potential of the Jayanti coast really needs to be given more attention by local governments to be developed, in order to improve the economy of Cianjur regency to be more prosperous.Keywords: Development; Tourism; Jayanti Tourism Potential; Tourism Potential.